The effect of Al-Wand lake on the shallow groundwater aquifer in Khanaqin area, Diyala Governorate, Iraq - Ibrahim, Ismail Ahmed; Al-Dabbas, Moutaz (Iraqi Journal of Science, 2022)
The relationship between Al-Wand lake and groundwater was studied in Khanaqin cityby identifying water levels for Al-Wand lake and the shallow groundwater aquifer for 2019 and 2020. The hydrochemical analyses of Al-Wand river water, Al-Wand lake water and shallow groundwater, and identifying the grain size analysis and mineralogy of the surface sediments have been done. This relationship was adopted on climate data of the study area by knowing which seasons contained water surplus or water deficit, and porosity and permeability define of soil that affects groundwater movement, and identify the salinity that effect on water quality.